2015
DOI: 10.1016/j.jpainsymman.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on a Protocol for Withdrawal of Life-Sustaining Measures on Two Non-Academic Intensive Care Units in The Netherlands: Few Signs of Distress, No Suffering?

Abstract: The end-of-life protocol seems effective in realizing adequate patient comfort. Most patients in whom life-sustaining measures are withdrawn are well sedated and show few signs of distress. Dosages of opioids and sedatives increase significantly during treatment withdrawal but do not contribute to time until death. Dying with a minimum of distressing signs is thus practically possible and ethically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…17,34,35 The latter indicates that patients in need of higher opioids dosages probably have better preserved neurological functions necessitating more opioids to maintain adequate end-of-life comfort care. 17,34,35 The latter indicates that patients in need of higher opioids dosages probably have better preserved neurological functions necessitating more opioids to maintain adequate end-of-life comfort care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,34,35 The latter indicates that patients in need of higher opioids dosages probably have better preserved neurological functions necessitating more opioids to maintain adequate end-of-life comfort care. 17,34,35 The latter indicates that patients in need of higher opioids dosages probably have better preserved neurological functions necessitating more opioids to maintain adequate end-of-life comfort care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on WLST practices showed either no influence or delayed moment of death with use of sedatives and analgesics. 17,34,35 The latter indicates that patients in need of higher opioids dosages probably have better preserved neurological functions necessitating more opioids to maintain adequate end-of-life comfort care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of family members during the PE must be evaluated as an exception, and needs preparation that involves the entire multidisciplinary team of the ICU. 19 In this study, patients submitted to PE had a fairly high average age (73.8 years). In a North American study, patients who were withdrawn from mechanical ventilation were also mostly elderly, with an average of 71 years.…”
Section: Discussionmentioning
confidence: 78%
“…Even more surprising is the fact that the authors do refer to the article of Kompanje et al 3 from 2008, in which a protocol for anticipation on symptoms of discomfort is discussed but not to the aforementioned article in which that very same protocol is evaluated in a two-year prospective intervention study. 2 Furthermore, in this study, pain also is labeled as a sign of distress. However, the presence of pain is already very difficult to evaluate in the normal critically ill (intubated and sedated) intensive care unit/ emergency room population, let alone in a population with severe cerebral trauma or even coma.…”
Section: Dear Editormentioning
confidence: 88%
“…In 2015, we published in this very same journal an article with the following title: An observational study on a protocol for withdrawal of life-sustaining measures in two non-academic intensive units in The Netherlands: few signs of distress, no suffering? 2 In this article, we describe both the incidence and severity of withdrawal of life-sustaining measurements-related stress symptoms like: terminal restlessness, congestion/stridor, and death rattle. Our study population comprises 241 patients, including 65 patients with a primary or a secondary (after cardiac arrest) neurological disease.…”
Section: Dear Editormentioning
confidence: 99%